A Training Program for Anthropometric Measurements by a Dedicated Nutrition Support Team Improves Nutritional Status Assessment of the Critically Ill Child*. Issue 3 (March 2015) - Valla, Frederic V.; Ford-Chessel, Carole; Meyer, Rosan; Berthiller, Julien; Dupenloup, Christine; Follin-Arbelet, Nathalie; Hubert, Anna; Javouhey, Etienne; Peretti, Noel
Abstract : Objectives: The cornerstone of an optimal nutrition approach in PICUs is to evaluate the nutritional status of any patient. Anthropometric measurements and nutritional indices calculation allow for nutritional status assessment, which is not often part of routine management, as it is considered difficult to perform in this setting. We designed a study to evaluate the impact of a training program by the PICU nutritional support team on the implementation of routine anthropometric measurements on our PICU. Design: A prospective study was performed over a 2-year period, which included: a baseline evaluation of nutritional assessment, knowledge, anthropometric measurements (weight, height, and head and mid upper arm circumferences), and nutritional indices calculation in patient files. This was followed by a training program to implement the newly developed nutrition assessment guidelines, which included anthropometrical measurements and also the interpretation of these. The impact of this nutritional assessment program was reviewed annually for 2 years after the implementation. Setting: PICU—Lyon, France. Patients and Subjects: PICU nursing and medical staff, and patients admitted in February 2011, 2012, and 2013. Interventions: Training program. Measurements and Main Results: Ninety-nine percent of staff ( n = 145) attended the individual teaching. We found significant progress in nutritional awareness and confidence about nutritional assessment following the teaching program. In addition, an improvement in staff knowledge about undernutrition and its consequences were found. We enrolled 41, 55, and 91 patients in 2011, 2012, and 2013, respectively. There was a significant increase in anthropometric measurements during this time: 32%, 65% ( p = 0.002), and 96% in 2013 ( p < 0.001). Nutritional indices were calculated in 20%, 74% ( p < 0.001), and 96% ( p < 0.001) of cases. Conclusions: This is the first study, showing that a targeted nutritional assessment teaching program that highlights both the importance and techniques of anthropometrical measurements has successfully been implemented in a PICU. It managed to improve staff knowledge and nutritional practice.